Basal Metabolic Rate and Ecology of Some Passerine Birds in Indonesia - Asep S Adhikerana; Dewi M Prawiradilaga (Media Konservasi, 1991)
Although the value of basal metabolic rate (BMR) is believed to be used as a basic reference in comparing several biological aspects of birds such as morphology, phylogeny, and ecology, its relationships with these aspects is hardly discussed. The paper is aimed to analyse relationships betwen the value of BMR and ecological aspects of some families of passerine birds in Indonesia whicch include nest type, primary food, primaly habitat, stratification of living site and foraging behavior. The results indicate that nest type, primexy food and foraging behavior have aclose relationship with the value of BMR of twenty five families of passerine birds; whereas the stratification of living site separate these birds families into two groups: arboreal and terrestrial groups. However, further research is still needed to verify these results.